2017
DOI: 10.1007/s10456-017-9572-7
|View full text |Cite
|
Sign up to set email alerts
|

Prox1-GFP/Flt1-DsRed transgenic mice: an animal model for simultaneous live imaging of angiogenesis and lymphangiogenesis

Abstract: The roles of angiogenesis in development, health, and disease have been studied extensively; however, the studies related to lymphatic system are limited due to the difficulty in observing colorless lymphatic vessels. But recently, with the improved technique, the relative importance of the lymphatic system is just being revealed. We bred transgenic mice in which lymphatic endothelial cells express GFP (Prox1-GFP) with mice in which vascular endothelial cells express DsRed (Flt1-DsRed) to generate Prox1-GFP/Fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 31 publications
1
30
0
Order By: Relevance
“…The symptoms of tongue cancer include a red or white patch on the tongue, pain while swallowing, and a constant sore throat (Xu et al 2017). Although advances have been made in the diagnosis and treatment of tongue cancer over the last decade, the morbidity and mortality in young patients (< 40 years old) have significantly increased (Zhong et al 2017). Moreover, the tumorigenesis of the tongue has not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…The symptoms of tongue cancer include a red or white patch on the tongue, pain while swallowing, and a constant sore throat (Xu et al 2017). Although advances have been made in the diagnosis and treatment of tongue cancer over the last decade, the morbidity and mortality in young patients (< 40 years old) have significantly increased (Zhong et al 2017). Moreover, the tumorigenesis of the tongue has not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…They found that lymphangiogenesis occurred even when angiogenesis did not, in concordance with previous studies reporting the occurrence of corneal lymphangiogenesis independently of hemangiogenesis . Conditional deletion of VEGFR2 in endothelial cells markedly reduced lymphangiogenesis in the mouse cornea in response to VEGF‐A and VEGF‐C pellets, compared to that in mice without this conditional deletion, suggesting a role for blood endothelial cell VEGFR2 in lymphatic vessel formation and growth . There seem to be various combinations of ligand‐binding affinities and kinase activities that produce a spectrum of downstream effects, both angiogenic and lymphangiogenic.…”
Section: Lymphangiogenesis Mechanisms: Major Target Sitessupporting
confidence: 83%
“…[118][119][120][121][122][123] Conditional deletion of VEGFR2 in endothelial cells markedly reduced lymphangiogenesis in the mouse cornea in response to VEGF-A and VEGF-C pellets, compared to that in mice without this conditional deletion, suggesting a role for blood endothelial cell VEGFR2 in lymphatic vessel formation and growth. 78 There seem to be various combinations of ligand-binding affinities and kinase activities that produce a spectrum of downstream effects, both angiogenic and lymphangiogenic. Thus, before a therapeutic target can be determined, it is crucial to further characterize the specific mechanisms of the VEGF signaling system.…”
Section: Vegf Pathwaymentioning
confidence: 99%
“…Finally, Zhong et al developed Prox1-GFP/Flt1-DsRed (PGFD) mice for refined tracking of both blood and lymphatic vascular changes over time, particularly the monitoring of corneal hemangiogenesis and lymphangiogenesis within individual mice throughout a 14-day period after corneal injury [51]. Using confocal microscopy and two-photon imaging, they rapidly visualized fluorescent three-dimensional blood and lymphatic vessel patterns up to 150 and 400 µm deep, respectively, in large, unprocessed specimens from many tissues.…”
Section: Lymphatic Imaging Using Transgenic Fluorescent Reporter Micementioning
confidence: 99%
“…( b) The percent areas occupied by alkali burn-induced corneal HA and LA were calculated over the experimental time course. Reprinted with permission from [51]. …”
Section: Figurementioning
confidence: 99%